Successful penile replantation after complete amputation and 23 hours ischaemia time: the first in reported literature - Henry, Nader (BMJ Case Rep, 2020)
Complete penile amputation is a rare and poorly documented injury with severe physical and psychosocial implications. Our institution presents a case of successful penile replantation following 23 hours of ischaemia time in a 34-year-old man with a history of paranoid schizophrenia who sustained a complete penile amputation during an act of deliberate self-harm. To the best of our knowledge, this is the longest documented ischaemia time for a successful penile replant in literature. The patient was able to achieve a full erection as early as 6 weeks postoperatively. Skin necrosis was noted as a common complication and this was successfully managed with debridement and skin grafting. Penile amputation injuries should be managed in a specialist centre with urological and plastic surgeons with expertise in microsurgical reconstruction. Penile replantation should be attempted, even if ischaemia time is prolonged, despite lower success rates given the significance of the injury to an individual.